Platelets and Their Role in the Pathogenesis of Cardiovascular Events in Patients With Community-Acquired Pneumonia - Feldman, Charles; Anderson, Ronald (Frontiers in Immunology, 2020)
Community-acquired pneumonia (CAP) remains an important cause of morbidity and mortality throughout the world with much recent and ongoing research focused on the occurrence of cardiovascular events (CVEs) during the infection, which are associated with adverse short-term and long-term survival. Much of the research directed at unravelling the pathogenesis of these events has been undertaken in the settings of experimental and clinical CAP caused by the dangerous, bacterial respiratory pathogen, Streptococcus pneumoniae (pneumococcus), which remains the most common bacterial cause of CAP. Studies of this type have revealed that although platelets play an important role in host defense against infection, there is also increasing recognition that hyperactivation of these cells contributes to a proinflammatory, prothrombotic systemic milieu that contributes to the etiology of CVEs. In the case of the pneumococcus, platelet-driven myocardial damage and dysfunction is exacerbated by the direct cardiotoxic actions of pneumolysin, a major pore-forming toxin of this pathogen, which also acts as potent activator of platelets. This review is focused on the role of platelets in host defense against infection, including pneumococcal infection in particular, and reviews the current literature describing the potential mechanisms by which platelet activation contributes to cardiovascular complications in CAP. This is preceded by an evaluation of the burden of pneumococcal infection in CAP, the clinical features and putative pathogenic mechanisms of the CVE, and concludes with an evaluation of the potential utility of the anti-platelet activity of macrolides and various adjunctive therapies.